National Parks and Rural Development : Practice and Policy in the United States - Edited By Machlis, Gary E; Field, Donald R. (Washington, D.C Island Press, 2000)
Thirteen chapters including literature reviews, case studies, and personal essays stress the overlooked role that US national parks can play in rural community economic development. Includes recommendations, questions for social science research, a guide to relevant federal programs, several maps, and b&w photos.
Illustrations, Maps
Keywords: Rural development -- United States -- Land use, Rural--Planning